Islamic Fintech for international trade finance with the application of wakalah smart contract - Adam Sa'ad, Auwal (2018)
Islamic Fintech is the most recent innovation in the advancement of Islamic Financial industry, the current evolution of Fintech markets in the world has proved to be the game changer in the banking and financial markets. International trade finance is one of the most important areas infiltrated by the Islamic Banking and finance institutions. However, the Islamic letter of credit initiated by many Islamic Banks were based on various Shari’ah principles that allow the bank benefiting from the transactions as agents or share in the business with the client as a joint venture business relationship. The emergence of Islamic Fintech has been a drastic progression in the Islamic banking and financial sector, the Islamic fintech becomes one of the most important mechanisms in the Islamic Financial industry to develop the International trade finance. Islamic Fintech helps in cost reduction, digitalization and automation and provides alternative financing options. This paper discusses the International trade finance and introduces wakalah model to be implemented through the newly innovated wakalah smart contract. The new model aimed at facilitating the international trade transactions with the use of innovative financial technology for international trade finance. This will help the Entrepreneurs, SME’s and the International Business players and the Islamic Financial Institutions in overcoming various challenges confronted by the International trade finance today. The newly wakalah smart contract will help execute the transactions in a fastest way than the conventional wakalah contract do, the paper discusses the Shari’ah issues related to the new Fintech enhancement in the Islamic financial sector.